Impact of employee value proposition towards job satisfaction of Petronas Human Capital Management staff / Ahmad Ikram Ajmain Abu Hassan - Abu Hassan, Ahmad Ikram Ajmain (Faculty of Business and Management, 2014)
Job Satisfaction has always been used as the indicator of how employees feel about their job and usually align with performance and motivation. The higher the job satisfaction, the happier the employees with their job. Low job satisfaction will lead to employee-related problem such as turnover, low performance and talent poaching. It usually will go through stress, depression and absenteeism before it contribute to more serious problem. Past studies shows that there are many factors that can affect employees’ job satisfaction. Yet this study covers the elements of PETRONAS’ Employee Value Propositions (EVP) which is Rewards, Growth & Trust. Compensation and Benefits under Rewards, and Career Growth under Growth of EVP have been selected for this study. This study covers PETRONAS Human Capital Management Staff and it involved 30 respondents across functions. Personally administered questionnaire were used to collect data in trying to find the impact of EVP towards their job satisfaction. From the data collected, it was found that compensation (monetary rewards) is the most influential factors that affect the employees’ job satisfaction. On the other hand, Career Growth have a moderate impact and the least influential towards the employees’ job satisfaction when compared to other elements studied.